2017
DOI: 10.1177/1010428317701648
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome analysis reveals dysregulated oncogenic lncRNAs in natural killer/T-cell lymphoma and establishes MIR155HG as a target of PRDM1

Abstract: Natural killer/T-cell lymphoma is a rare but aggressive neoplasm with poor prognosis. Despite previous reports that showed potential tumor suppressors, such as PRDM1 or oncogenes associated with the etiology of this malignancy, the role of long non-coding RNAs in natural killer/T-cell lymphoma pathobiology has not been addressed to date. Here, we aim to identify cancer-associated dysregulated long non-coding RNAs and signaling pathways or biological processes associated with these long non-coding RNAs in natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 67 publications
0
35
0
Order By: Relevance
“…lncRNA MIR155HG can suppress lymphoma by regulating the activity of NF-κB and mesenchymal genes [42]. However, the contribution of lncRNA DNM1P35 to the development of KIRC is still not known, and further studies are required to address these aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lncRNA MIR155HG can suppress lymphoma by regulating the activity of NF-κB and mesenchymal genes [42]. However, the contribution of lncRNA DNM1P35 to the development of KIRC is still not known, and further studies are required to address these aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that lncRNA MIR155HG plays key roles in the development of myeloproliferative disorders, leukemia, lymphoma, and glioma [40][41][42]. lncRNA MIR155HG can suppress lymphoma by regulating the activity of NF-κB and mesenchymal genes [42].…”
Section: Discussionmentioning
confidence: 99%
“…Kucuk et al (7) found that STAT3 and STAT5B were each mutated at 5.9% frequency (n = 51). Baytak et al (22) focused on the dysregulated oncogenic lncRNA (MIR155HG) in NKTCL by analyzing the SRP049695 dataset. In this study, we found that ECM receptor interaction pathway was significant in KEGG ( Figure 1D), PPI network (Figure 3), and GSEA (Figure 2A) analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al [51] reported ZFAS1 was upregulated in AML cell lines compared with T lymphocytic leukemia cell line or Burkitt’s lymphoma cell line, then they found knockdown of ZFAS1 impeded proliferation, and promoted apoptosis of AML cell line. Baytak et al [52] found ZFAS1 was overexpressed in NKTCL tissues and ZFAS1 -associated genes are enriched in pathways regulating proliferation and survival. The above data showed ZFAS1 might act as a valuable prognostic biomarker and potential therapeutic target for Melanoma, NSCLC, OS, ESCC, AML and NKTCL.…”
Section: Zfas1 In Various Cancersmentioning
confidence: 99%